2017
DOI: 10.1016/j.jtho.2016.11.400
|View full text |Cite
|
Sign up to set email alerts
|

MA04.05 P53 Non-Disruptive Mutation is a Negative Predictive Factor for OS and PFS in EGFR M+ NSCLC Treated with TKI

Abstract: incidence of grade 3 diarrhea was 12% with neratinib and 14% with neratinib + temsirolimus, which lasted for a median duration of 1.5 (interquartile range, 1.0-2.0) days and 4.0 (interquartile range, 2.0-16.0) days, respectively. Conclusion: Neratinib (240 mg/day) + temsirolimus (8 or 15 mg/week) produced responses lasting 2 to 18+ months in 19% of patients with HER2-mutant lung cancers. Correlative data will be presented at the meeting. Diarrhea was manageable with loperamide prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…We could not confirm the correlation between TP53 mutation and shorter PFS that has been reported by different preliminary studies [10,16,17,18,19,33]. The frequency of TP53 mutations was only 17.3% in our cohort whereas it ranged between 30.1% and 62% in the above mentioned reports.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…We could not confirm the correlation between TP53 mutation and shorter PFS that has been reported by different preliminary studies [10,16,17,18,19,33]. The frequency of TP53 mutations was only 17.3% in our cohort whereas it ranged between 30.1% and 62% in the above mentioned reports.…”
Section: Discussioncontrasting
confidence: 97%
“…In addition, patients carrying somatic mutations in the PI3K/AKT/mTOR pathway had a shorter PFS and overall survival (OS) when compared to patients without mutations. Finally, different studies have suggested that mutations in TP53 are associated with shorter PFS in EGFR mutant NSCLC patients receiving treatment with EGFR TKIs [7,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%